2013
DOI: 10.1093/cercor/bht022
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Modules of Coherent Activity in Pathway-Specific LFPs in the Hippocampus Reflect Topology and Different Modes of Presynaptic Synchronization

Abstract: Ongoing network activity often manifests as irregular fluctuations in local field potentials (LFPs), a complex mixture of multicellular synaptic currents of varying locations and extensions. Among other conditions, for synchronously firing presynaptic units to generate sizable postsynaptic LFPs, their axonal territories should overlap. We have taken advantage of anatomical regularity of the rat hippocampus and combined multiple linear recordings and spatial discrimination techniques to separate pathway-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(143 citation statements)
references
References 54 publications
5
138
0
Order By: Relevance
“…Another IC ( lm ) corresponded to a current sink in str. lacunosum-moleculare (Figure 1B, D; Brankack et al, 1993; Benito et al, 2014), the site of EC3 axon terminals. In contrast to the other two ICs, which were dominated by current sinks in the dendritic layers, the third component ( CA1pyr ) had a current source at the CA1 str.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another IC ( lm ) corresponded to a current sink in str. lacunosum-moleculare (Figure 1B, D; Brankack et al, 1993; Benito et al, 2014), the site of EC3 axon terminals. In contrast to the other two ICs, which were dominated by current sinks in the dendritic layers, the third component ( CA1pyr ) had a current source at the CA1 str.…”
Section: Resultsmentioning
confidence: 99%
“…lacunosum-moleculare occur, on average, at the peak of the theta cycle (Buzsáki et al, 1986; Brankack et al, 1993; Kamondi et al, 1998; Montgomery et al, 2009; Mizuseki et al, 2009; Benito et al, 2014), before the dominant CA3-mediated gamma S on the descending phase of theta (Figure 3E). Furthermore, the theta-phase separation of EC3 spiking (Mizuseki et al, 2009) and gamma oscillations (Figure 3) at the theta peak, and the CA1 spiking (Mizuseki et al, 2009) and perisomatic fast-gamma patterns (Figure 3) at the theta trough (Colgin et al, 2009; Belluscio et al, 2012), implies that fast gamma activity may not be used effectively as a mechanism of communication between CA1 and its afferent regions.…”
Section: Discussionmentioning
confidence: 99%
“…The most influential factors are the geometry of individual neurons, their three-dimensional arrangement, and the distribution of activating synaptic inputs on individual cells and the population as a whole. The variable contributions and combinations of these factors in different brain structures make LFPs large or small, positive or negative, and they may reflect active or passive synaptic currents, reaching locations far from the source or remaining local, and they may or may not be related to the afferent input (Benito et al, 2013; Fernández-Ruiz et al, 2013). …”
Section: Local Field Potentials In Simple and Complex Structuresmentioning
confidence: 99%
“…Before we can use the time fluctuations of an ICA-derived LFP component in a quantitative manner, its pathway-specificity must be proven. This can be explored through cross-checking with additional data, such as correlation with spikes in the population of origin, postsynaptic pharmacology, modulation of afferent populations, matching to evoked activity and to anatomical data (Korovaichuk et al, 2010; Fernández-Ruiz et al, 2012: for a detailed explanation on the limitations and practical hints for their solution, see Makarova et al, 2011; Benito et al, 2013). In the hippocampus we reported that all but one of the major ICA-derived components are pathway-specific and correspond to known local and distant afferent excitatory and inhibitory populations (Korovaichuk et al, 2010; Benito et al, 2013).…”
Section: Local Field Potentials In Simple and Complex Structuresmentioning
confidence: 99%
“…During different behaviors, those theta dipoles are coordinated in a variable manner ) modulating the spiking of hippocampal neurons accordingly. Pharmacological manipulations have been proven useful to dissociate and characterize the different synaptic generators of the theta rhythm in the hippocampus and other areas (Vanderwolf, 1988;Soltesz and Deschenes, 1993;Newman et al, 2013;Benito et al, 2014) but a comprehensive understanding of its mechanisms is still lacking.…”
Section: Aggregate Activity Patterns Of Neuronal Populationsmentioning
confidence: 99%